Eksistensi Putusan Penyelesaian Sengketa oleh Komisi Informasi Provinsi Jambi dalam Pemenuhan Hak Memperoleh Informasi Publik - Yanti, Herma; Zamzimi, Padlan; Havid, Meutia (Wajah Hukum, 2025)
The dispute resolution decision by the Information Commission is expected to encourage the emergence of information disclosure by Public Agencies that previously did not provide access to Applicants who needed the information. Considering that previously the Applicant had gone through the procedures and the length of time determined by law from submitting an application to the targeted Public Agency, submitting an objection to the Superior of the Public Agency concerned to the request for dispute resolution at the Jambi Provincial Information Commission, among others. The purpose of this study is to determine how the existence of the dispute resolution decision by the Jambi Provincial Information Commission on the fulfillment of the Applicant's right to obtain public information. This research is normative juridical with an approach of 43 decisions of the Jambi Provincial Information Commission from 2022 to 2024. The data was collected through a study of decision documents and analyzed qualitatively. The results show that most of the dispute resolution decisions provide a large space for the fulfillment of the Applicant's right to obtain the necessary information. Various information that was previously closed to the applicant is declared through the decision as open information. And of the decisions rejecting the application, which is also quite a large number, most of the reasons are because the dispute application submitted by the applicant is not within the scope of the Information Commission's authority. In other words, only a small part of the rejection decisions are because they confirm the decision of the Public Agency that refused to provide the information requested by the Applicant.